First rider's call - Britain, Kristen (Green Rider - book 2., 2003)
Karigan G'Ladheon was a green Rider, one of the King of Sacoridia's magical messengers. With evil forces at large in the kingdom and the messenger service depleted and weakened, can Karigan reach through the veils of time to get help from the First Rider, a woman who has been dead for a thousand years?